1977
DOI: 10.1111/j.1095-8339.1977.tb01177.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of sex determination in Equisetum: an analysis of regeneration in gametophytes of the subgenus Equisetum

Abstract: Equisetum gametophytes possess extensive powers of regeneration without showing any signs of diminished vigour or abnormal development. Isolated lamellae, pieces of antheridial and archegonial branches were used to analyse gametophyte morphogenesis and sex determination. Intact individuals and subcultured sexual branches never revert to a vegetative state. Transplantation of apical pieces of archegonial branches on to fresh medium delays the onset of antheridium formation indicating phenotypic control. O n the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
3
10
0
1
Order By: Relevance
“…Data on the sexuality of cultured gametophytes are taken from Duckett (1968Duckett ( , 1970aDuckett ( , 1977 where details ofmedia and conditions are also given.…”
Section: Sampling Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Data on the sexuality of cultured gametophytes are taken from Duckett (1968Duckett ( , 1970aDuckett ( , 1977 where details ofmedia and conditions are also given.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…With the knowledge that the sex change of initially female Equisetum gametophytes to antheridium formation is mediated by accumulation of metabolites in culture (Duckett, 1977) a factor clearly of much lesser importance in nature, the rarity o f wild bisexual individuals is readily explained. The latter situation is almost certainly one of'the principle reasons why many early workers described the gametophytes as strictly dioecious.…”
Section: Gametophyte Morphogenesis and Sexual Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…A case of complete ESD (i.e., no evidence of GSD) was reported in Equisetum sp., a horsetail with haplo‐diploid life cycle. Indeed, it was shown that haploid gametophytes were potentially bisexual (Duckett 1977), and that sex expression was, at least partly, determined by environmental factors (Guillon and Fievet 2003). Other mechanisms involved in sex determination evolved in the fern Ceratopteris richardii , where male:hermaphrodite ratios are determined epigenetically by an antheridiogen pheromone; thus, male frequencies increased with the density of the population (Tanurdzic and Banks 2004).…”
mentioning
confidence: 99%